The longitudinal link between visual acuity and health-related quality of life in patients with diabetic retinopathy - Matza, Louis S; Rousculp, Matthew D; Malley, Karen; Boye, Kristina S; Oglesby, Alan (Health and quality of life outcomes, 2008)
Background This study characterized the degree of change in health-related quality of life (HRQL) associated with change in visual acuity among patients with diabetic retinopathy. Methods Data are from a randomized, placebo-controlled trial of ruboxistaurin for vision loss in patients with diabetic retinopathy. Visual acuity was quantified as letters on the ETDRS visual acuity chart. HRQL was assessed with the 25-Item Visual Function Questionnaire (VFQ-25) and the SF-36. Patients were categorized into groups based on visual acuity change from baseline to month 18. HRQL change of these groups was compared using general linear models. Regression analyses examined visual acuity change defined continuously. Results Patients (N = 535) were primarily Caucasian (81.9%) and male (64.1%); mean age = 59.3 years. Compared to patients whose visual acuity did not change, the group with > 10 letters vision loss had significantly greater decreases in all VFQ-25 subscales except ocular pain. SF-36 change scores did not correspond as closely to change in vision. Change in visual acuity defined continuously was significantly associated with change in all VFQ-25 scales except ocular pain (p < 0.0001). Conclusion Change in visual acuity was associated with corresponding changes in HRQL among patients with diabetic retinopathy. Previous research has often defined vision loss as a loss of at least 15 letters on the ETDRS visual acuity chart. In the current study, however, a loss of at least 10 letters was associated with substantial declines in HRQL domains such as driving, dependency, role limitations, and mental health. These findings suggest that patients who experience vision loss of at least 10 letters may be appropriate targets of future research and clinical intervention.